2010
DOI: 10.1088/0264-9381/27/16/165012
|View full text |Cite
|
Sign up to set email alerts
|

Geometric finiteness, holography and quasinormal modes for the warped AdS 3 black hole

Abstract: We show that there exists a precise kinematical notion of holography for the Euclidean warped AdS 3 black hole. This follows from the fact that the Euclidean warped AdS 3 black hole spacetime is a geometrically finite hyperbolic manifold. For such manifolds a theorem of Sullivan provides a one-to-one correspondence between the hyperbolic structure in the bulk and the conformal structure of its boundary. Using this theorem we obtain the holographic quasinormal modes for the warped AdS 3 black hole.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…As discussed above, another manifestation of the holography for the BTZ black hole appears through its connection with Sullivan's theorem [49,58,59]. It was shown in [60] JHEP06 (2017)107 that instead of using the boundary conditions at infinity, certain monodromy conditions could be imposed on the solutions of a massless KG equation in the background of a BTZ black hole to give exactly the same QNM frequencies.…”
Section: Qnm and Holographymentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed above, another manifestation of the holography for the BTZ black hole appears through its connection with Sullivan's theorem [49,58,59]. It was shown in [60] JHEP06 (2017)107 that instead of using the boundary conditions at infinity, certain monodromy conditions could be imposed on the solutions of a massless KG equation in the background of a BTZ black hole to give exactly the same QNM frequencies.…”
Section: Qnm and Holographymentioning
confidence: 99%
“…Further evidence for holography in the case of the BTZ comes from Sullivan's theorem, which says that for a certain class of manifolds, there is a 1-1 correspondence of the hyperbolic structure as encoded in the metric and the conformal structure of the boundary [57]. It has been shown that the Sullivan's theorem is applicable for the BTZ black hole [49,58,59], which provides an exact kinematical statement of holography for the BTZ. Furthermore, using certain monodromy conditions which can be derived using the Sullivan's theorem, it is possible to calculate the so called nonquasinormal frequencies for the BTZ black hole, which have a form that is identical to the usual QNM frequencies for the BTZ [60,61].…”
Section: Qnm and Holographymentioning
confidence: 99%
“…Following the argument of Ref. 31, we obtain so-called holographic quasinormal mode frequencies of the warped AdS 3 black hole as follows:…”
Section: Holographic Quasinormal Modes As Characteristic Modes Of Blamentioning
confidence: 99%
“…Following the argument of Ref. 57, we obtain so-called holographic QNM frequencies of the warped AdS 3 black hole as follows:…”
Section: Holographic Qnm As Characteristic Modes Of Black Holesmentioning
confidence: 99%